Evaluation of a tactile breath pacer for sleep problems: A mixed method pilot study - Sascha Vermeylen; Elisabeth Honinx; Stefanie Broes; Hilde Vandenhoudt; Nele A. J. De Witte (Frontiers Media S.A., 2022)
Sleep problems, like insomnia, are a prevalent condition associated with major health risks. Prevention and treatment of sleep problems are thus essential to preserve physical and mental health. Previous work supports the effectiveness of breathing guidance for sleep problems and recommends breathing exercises as an effective intervention for insomnia. While new technologies can support breathing guidance, such novel devices should be assessed for effectiveness and usability to facilitate implementation and continued use. The current pilot study investigates the acceptability and usability of a mobile tactile breathing device and explores its potential impact on subjective sleep quality. In this mixed-method pilot study, 39 participants tested the breathing device for one month in naturalistic circumstances. We collected their experiences, subjective sleep quality, and feedback regarding the usability of the device and the accompanying app through a survey in a pre-post design. The results show that the breathing device is an acceptable solution for sleep problems and participants particularly appreciate the standalone function and design. Nevertheless, important points of attention, such as the size of the device, were also identified. Explorative analyses suggest that subjective sleep quality improved after using the device and accompanying app. The current study supports the usability and acceptability of a tactile breath pacer and provides preliminary evidence supporting a positive impact of the technology on the sleep quality of participants. Recommendations for developers of breathing technologies and eHealth are devised based on the findings.